Path Analysis Of Academic The University of Islam Bandung Performance Blended Learning - Ramdani, Yani; Syam, Nia Kurniati; Hamdani, Erwin Harahap (Annpublisher, 2025)
This study aims to investigate the relationship between self-regulated learning, creative performance, and early mathematical proficiency in the academic success of college students. The methods of this study are to compare the assessments and surveys conducted before and throughout the educational process. Learning activities are executed through both in-person and online formats. In-person instruction is performed according to the university's established lecture timetable. E-learning is conducted via organized tasks and autonomous assignments. Data were collected from college students in the University of Islam Bandung calculus course. The findings indicated that self-regulated learning and early mathematics aptitude significantly influenced student academic achievement, whereas the impact of creative performance was comparatively less pronounced. Self-regulated learning influences academic success by 38.76%, while early mathematical competence affects academic performance by 30.96%. Consequently, self-regulated learning significantly influences academic performance more than initial mathematical competence.